The Role of K-Pop Idols in the Consumptive Lifestyle of Adolescents in an Islamic Perspective - Mulya, Berlian Dwi Puji; Nasikhin; Junaedi, Mahfud; Fihris (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2024)
This study aims to examine the influence of K-pop idols on adolescent consumer behaviour and explore Islamic views in responding to the consumption patterns of adolescents who like K-pop idols. The research method used was qualitative, and data was collected through questionnaires and literature reviews. Data validation was carried out using source triangulation techniques. The data analysis used is the Miles and Huberman model, which includes data reduction, presentation, and conclusion. The study results show that K-pop idols play a significant role in shaping adolescents' consumer lifestyles, as seen from their willingness to spend money to buy albums, photocards, or other items related to their idols. This consumer tendency is also reflected in purchasing fashion products that imitate their idols' clothing styles. In the Islamic perspective as stated in QS. Al-A'raf verse 31 and QS. Al-Ahzab verse 59 explains that this consumer lifestyle needs to be consistent with the principles that emphasize the importance of maintaining balance in using wealth. These findings indicate the importance of formulating educational policies that encourage K-pop-loving teenagers to make wiser financial decisions based on Islamic teachings. Thus, this study adds insight into the influence of pop culture on consumer behavior and provides a basis for interventions that support healthy financial management within the framework of religious values.